Embodied energy in existing buildings as a tool for sustainable intervention on urban heritage. (January 2023) - Guidetti, Elena; Ferrara, Maria
Highlights: Energy stored in our urban heritage is rarely considered in existing literature. Embodied energy in existing buildings is reframed in new lifecycle system boundary. Decision-making scope and time drive consideration of embodied energy quantities. A new embodied-energy conscious paradigm for decision at urban level is proposed. New research questions for retroactive embodied energy definition and calculation. Abstract: In the context of worldwide efforts towards energy efficiency and circular economy, embodied energy has been increasing its weight in the total lifecycle energy use of buildings. By investigating the context and the extent to which it is crucial to calculate embodied energy quantities for existing buildings, this paper investigates the concept itself of embodied energy in existing buildings as an untapped potential for driving sustainable renovation and reuse of urban environments. A new research gap concerning the embodied energy in existing buildings emerges from a critical literature review. A new comprehensive approach for definition and calculation of embodied energy that integrates both retroactive and prospective perspectives is proposed within two boundary systems expressed in terms of life-cycle energy analysis.This approach outlines the potential role of embodied energy in supporting decision at city-level regarding adaptive reuse or demolish-rebuild scenarios on buildings as part of urban heritage. Results investigates the extent to which embodied energy stored in our urban heritage should be considered as a decision parameter to prioritize preservation and reuse interventions among the large number of existing buildings composing the present and the future built environment, delineating new open issues for further research.